2013
DOI: 10.1080/10408398.2012.680078
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Probiotics on the Skin

Abstract: Skin is the largest organ of the body and is constantly exposed to physical, chemical, bacterial, and fungal challenges. It is well known that probiotics are helpful for specific disorders and different clinical studies have indicated that probiotics have special effects in cutaneous apparatus directly or indirectly that can be considerable from versatile aspects. Probiotic bacteriotherapy can have great potential in preventing and treating the skin diseases including eczema, atopic dermatitis, acne, and aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 183 publications
0
57
0
2
Order By: Relevance
“…Some studies [82,147] have found that postoperative consumption of probiotics (mainly L. plantarum 299) per os improves immune response, reduces the number of postoperative infections, and reduces hospitalization time and the amount of prescribed antibiotics. All of these studies conclude that postoperative endpoints should continue to be thoroughly investigated, and two studies went on to highlight the great potential of topical use of probiotics to protect the wound [15,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [82,147] have found that postoperative consumption of probiotics (mainly L. plantarum 299) per os improves immune response, reduces the number of postoperative infections, and reduces hospitalization time and the amount of prescribed antibiotics. All of these studies conclude that postoperative endpoints should continue to be thoroughly investigated, and two studies went on to highlight the great potential of topical use of probiotics to protect the wound [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Using various state-of-the-art molecular and genetic-based methods, it was found that the skin microbiota is dominated by bacteria from the phyla Actinobacteria, Firmicutes, Proteobacteria, and Bacteroidetes; resident genera mainly include Propionibacterium spp., Staphylococcus spp., Micrococcus spp., Corynebacterium spp., and Acinetobacter spp. and the main representatives of the fungi being species of the genus Malassezia [15][16][17][18]. e diversity of skin microbiota among individuals depends on age, diet, gender, and environmental and geographical factors.…”
Section: Skin Microbiotamentioning
confidence: 99%
“…8,9 The immune system of neonatal infants is not completely developed and is disposed to an immature T-helper type Th2-dominant state. 11 Probiotics have also been found to modulate specific and nonspecific immune responses to allergens by affecting phagocytosis and the production of proinflammatory cytokines and IgA. It has been demonstrated that appropriate microbial stimulation in early life contributes to the establishment of a balanced immune system.…”
mentioning
confidence: 99%
“…This figure also outlines possible mechanisms of probiotics action in skin, female urogenital tract, and respiratory tract. It includes modulation of the systemic immune function, competitive exclusion of harmful microorganisms, production of antimicrobial substances and growth substrates, inhibition of bacterial toxin production, among others (Bermudez-Brito et al 2012;Gogineni et al 2013;Markowiak and Śliżewska 2017;Rahmati Roudsari et al 2013).…”
Section: Potential Mechanisms Of Probiotics Actionmentioning
confidence: 99%
“…Possible mechanisms of probiotic action in the skin, female urogenital tract, and respiratory tract. Adapted from RahmatiRoudsari et al (2013) …”
mentioning
confidence: 99%